1236 Supporting the Schooling of Very Preterm Children: Education Professionals' Opinions and Information Needs. (October 2012) - Henderson, D; Beer, C; Wolke, D; Johnson, S
Abstract : Background and Aims: Increasing numbers of very preterm (VP; < 32 weeks) children with special educational needs are entering, and challenging, the education system. At present we know little about teachers' information needs or opinions regarding how to support these children. Methods: Preschool and primary education professionals completed a questionnaire to elicit opinions regarding their information needs, disclosure of birth status and delayed school entry for VP children. Respondents rated how strongly they agreed with 10 statements using a 5-point Likert scale; responses ranged from strongly agree to strongly disagree. Additional questions explored training received and demographic information. Results: Of the 120 respondents, 89% felt they were likely to teach a VP child and that educational management was the role of the class teacher. However, only 6% reported having received sufficient training about VP children and >90% agreed they would like more information about strategies to support VP children's learning. 92% of respondents agreed that disclosing a child's preterm birth status would be beneficial and none felt it would lead to problems associated with labelling. A small majority of teachers were supportive of parents delaying (56%) or deferring (58%) their child's school entry. Conclusions: This survey revealed that a worrying number of early years' education professionals received no formal training regarding the educational needs of VP children and most felt inadequately equipped to support these children in their classroom. There is a pressing need for clinicians to communicate evidence-based findings to facilitate ongoing management of VP children at school.